2022
DOI: 10.3389/fimmu.2022.884592
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral cytokine levels as novel predictors of survival in cancer patients treated with immune checkpoint inhibitors: A systematic review and meta-analysis

Abstract: BackgroundEarly identification of patients who will benefit from immune checkpoint inhibitors (ICIs) has recently become a hot issue in cancer immunotherapy. Peripheral cytokines are key regulators in the immune system that can induce the expression of immune checkpoint molecules; however, the association between peripheral cytokines and the efficiency of ICIs remains unclear.MethodsA systematic review was conducted in several public databases from inception through 3 February 2022 to identify studies investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 64 publications
2
11
0
Order By: Relevance
“…TIGIT could induce DCs to acquire an immature tolerogenic phenotype by triggering CD155, resulting in elevated IL-10 secretion and concomitant reduction in IL-12 production [ 25 ]. Since it prevents APCs from upregulating molecules involved in antigen presentation, IL-10 is critical for suppressing immune responses, thereby suppressing T cell proliferation and elaboration of immunostimulatory cytokines such as IFN-γ directly [ 50 , 51 ].…”
Section: The Central Role Of Tigit In the Cancer Immunotherapymentioning
confidence: 99%
“…TIGIT could induce DCs to acquire an immature tolerogenic phenotype by triggering CD155, resulting in elevated IL-10 secretion and concomitant reduction in IL-12 production [ 25 ]. Since it prevents APCs from upregulating molecules involved in antigen presentation, IL-10 is critical for suppressing immune responses, thereby suppressing T cell proliferation and elaboration of immunostimulatory cytokines such as IFN-γ directly [ 50 , 51 ].…”
Section: The Central Role Of Tigit In the Cancer Immunotherapymentioning
confidence: 99%
“…It is well known that in cancer patients, higher levels of IL-10 in serum correlate inversely with oncologic prognosis (34,35). Despite this, it has recently been observed that IL-10 may play a role in CD8 + T cell activation and proliferation in cancer and chronic in ammation (34). In addition, IL-10 and PD-1 play immunosuppressive roles through very different pathways (35), and dual blockade has synergistic antitumor action (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Identifying biomarkers to better select responders is an important goal [ 30 ]. Mao et al, in a meta-analysis of 22 studies, found that the pre-treatment peripheral cytokine levels of IL-6 and IL-8, but not IFN-γ, are predictors of worse OS of cancer patients treated with immune checkpoint inhibitors [ 31 ]. Additionally, one potential therapy is represented by the production of an anti-PDL1 vaccine that blocks PD-1/PD-L1 interaction, as a promising new therapeutical approach [ 32 ].…”
Section: Discussionmentioning
confidence: 99%